Primary Dural Lymphoma Mimicking En Plaque Cerebellopontine Angle Meningioma - Mei Xu; Ashish Bains; Yuan Rong (Case Reports in Pathology)
Primary dural lymphoma (PDL) usually arises from the calvarial dura without the brain parenchyma or systemic involvement and thus may not be considered as a typical form of primary CNS lymphoma (PCNSL). It is exceedingly rare. When it occurs, it might not be suspected as a primary diagnosis on clinical and radiologic findings. We present a PDL case that occurs at the cerebellopontine (CP) angle mimicking en plaque meningioma. The tumor histopathology showed a lymphoproliferative disorder immunophenotypically consistent with a low-grade marginal zone lymphoma. Bone marrow and systemic involvements were not identified, and a diagnosis of PDL was established. As a residual tumor at the CP angle was inaccessible to surgery, postoperative radiation therapy was performed. No recurrence was found at 15-month follow-up. PDLs are mostly indolent and have a good prognosis. There is no doubt that the most important differential diagnosis is meningioma. Furthermore, the present case emphasizes the necessity of an intraoperative consultation and knowledge of this rare yet essential form of PCNSL so that appropriate studies can be ordered.